CONTEXTUAL LEARNING MODEL PRACTICE - Paputungan, Frezy; siradjang, marshela (JCI Publisher, 2025)
Observation of Elementary School Students 14 Bone Bolango Selatan In grade 5 students using the Quiziz learning model along with the Game Based Learning method. The contextual learning model (Contextual Teaching and Learning/CTL) is a learning approach that emphasizes the relationship between subject matter and real-life situations of students. This model aims to help students understand academic concepts by connecting the knowledge gained from school with its application in everyday life, both in personal, social, and cultural contexts. Through contextual learning, teachers act as facilitators who encourage students to actively build knowledge and skills through direct experience, problem solving, and collaboration in learning communities. Contextual learning integrates several main components, including constructivism, inquiry (discovery), asking, learning communities, modeling, reflection, and authentic assessment. This approach requires students to think critically, creatively, and innovatively, and be able to relate learning materials to real problems faced in their environment. Thus, learning outcomes are expected to be more meaningful, increase motivation, and equip students with adaptability and problem solving skills that are relevant to future life.